The Syrian conflict and infectious diseases. Issue 6 (2nd June 2016) - Ozaras, Resat; Leblebicioglu, Hakan; Sunbul, Mustafa; Tabak, Fehmi; Balkan, Ilker Inanc; Yemisen, Mucahit; Sencan, Irfan; Ozturk, Recep
ABSTRACT: The conflict in Syria is a big humanitarian emergency. More than 200, 000 Syrians have been killed, with more than half of the population either having been displaced or having immigrated. Healthcare has been interrupted due to the destruction of facilities, a lack of medical staff, and a critical shortage of life-saving medications. It produced suitable conditions leading to the re-emergence of tuberculosis, cutaneous leishmaniasis, polio, and measles. Lebanon and Jordan reported increased rates of tuberculosis among Syrian refugees. Cutaneous leishmaniasis outbreaks were noted not only in Syria but also in Turkey, Jordan, and Lebanon. After a polio-free 15 years, Syria reported a polio outbreak. Ongoing measles outbreaks in the region was accelerated by the conflict. Iraq declared a cholera outbreak among the Syrian refugees. The healthcare facilities of the countries hosting immigrants, mainly Turkey, Lebanon, Jordan, Iraq, and Egypt, are overburdened. The majority of the immigrants live in crowded and unsanitary conditions. Infectious diseases are big challenges for Syria and for the countries hosting immigrants. More structured support from international organizations is needed for the prevention, control, diagnosis, and treatment of infectious diseases.